Gypenoside XLIX inhibiting PI3K/AKT/FOXO1 signaling pathway mediated neuronal mitochondrial autophagy to improve patients with ischemic stroke - Liu, Yonglei; Mao, Hongdie; Sha, Zhengguang; Zhao, Jishuai; Cai, Hui; Xi, Rong; Zhao, Zhenzhu; Yin, Xiaoling; Yang, Lin; Liu, Changyun (Frontiers in Pharmacology, 2025)
IntroductionIschemic stroke is a leading cause of mortality and disability worldwide, with limited therapeutic options and high rates of recurrence. Mitochondrial dysfunction plays a critical role in neuronal injury during ischemia-reperfusion, making mitochondrial autophagy a potential therapeutic target. Gypenoside XLIX, a major active metabolite of Gynostemma pentaphyllum, exhibits antioxidant and organ-protective properties, but its effects on neuronal mitochondrial damage in stroke remain unclear. This study aimed to explore the neuroprotective mechanisms of Gypenoside XLIX in ischemic stroke, focusing on the PI3K/AKT/FOXO1 signaling pathway.MethodsNeuroprotective effects were evaluated in oxygen-glucose deprivation (OGD) neuronal cells and middle cerebral artery occlusion (MCAO) rat models. Cell viability, apoptosis, ROS production, mitochondrial membrane potential, and autophagic flux were assessed by CCK-8, flow cytometry, ELISA, TMRE staining, immunofluorescence, and Western blotting. Signaling pathway involvement was examined using PI3K inhibitor LY294002, AKT activator SC79, and FOXO1 knockdown.ResultsGypenoside XLIX significantly improved neuronal viability (p < 0.01), reduced apoptosis (p < 0.01), and decreased ROS levels (p < 0.001) in OGD cells. It enhanced p-PI3K and p-AKT expression while suppressing FOXO1 (p < 0.05), promoted Beclin-1, LC3, PINK1, and Parkin expression (p < 0.001), and reduced p62 (p < 0 .01). In MCAO rats, Gypenoside XLIX decreased infarct volume (p < 0.001), brain edema (p < 0.01), and TUNEL-positive cells (p < 0.001), while elevating mitochondrial membrane potential and antioxidant enzyme levels (SOD, GSH-Px, CAT; all p < 0.001).ConclusionGypenoside XLIX alleviates ischemic stroke injury by activating the PI3K/AKT/FOXO1 pathway, enhancing mitochondrial autophagy, and reducing oxidative stress, supporting its potential as a novel neuroprotective agent in stroke management.